Impact de la couverture neigeuse sur l'estimation de l'épaisseur de la banquise par altimétrie - Hippert-Ferrer, Alexandre; Fleury, Sara; Guerreiro, Kévin; Chevalier, Matthieu; Zakharova, Elena; Rémy, Frédérique (CCSD, 2016)
International audience